The influence of recruitment age and anthropometric and physical characteristics on the development pathway of English academy football players - Noon, M. R.; Eyre, E. L. J.; Ellis, M.; Myers, T. D.; Morris, R. O.; Mundy, P. D.; Penny, R.; Clarke, N. D. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate the influence of recruitment age on retention and release across the development pathway and to explore the influence of anthropometric and physical characteristics on retention and release at different ages throughout the development pathway and the likelihood of obtaining a professional contract. Methods: Following receipt of ethics approval, a cross-sectional study tracking 4 cohorts of players over 5 years assessed 76 male youth football players (11-16 y) from an English football academy on 3 occasions annually in anthropometry, countermovement jump height, and linear (30 and 15 m) and multidirectional sprint time. Players were categorized based on their start and release date. Results: Starting early (ie, before U12) in an academy was a key indicator of obtaining a professional contract, representing 87% of the players signed. Bayesian regression models suggest that the majority of differences in physical characteristics between players that were released and retained are trivial, small, and/or uncertain. Players who attained a professional contract at 18 had slower 15- and 30-m sprint times at U13 to U15 (P > 0 = .87-.99), slower multidirectional sprint times at U14 (P > 0 = .99), and lower countermovement jump height at U13 to U16 (P > 0 = .88-.99) compared with players who did not gain a contract. Conclusion: Players recruited early have an increased likelihood of gaining a professional contract. Physical assessments lack utility when used in isolation as a talent-identification tool.